Oral amoxicillin‐clavulanate for treating diabetic foot infections. Issue 6 (12th March 2019) - Gariani, Karim; Lebowitz, Dan; Kressmann, Benjamin; von Dach, Elodie; Sendi, Parham; Waibel, Felix; Berli, Martin; Huber, Tanja; Lipsky, Benjamin A.; Uçkay, Ilker
Abstract : Aim: To assess amoxicillin‐clavulanate (AMC) for the oral therapy of diabetic foot infections (DFIs), especially for diabetic foot osteomyelitis (DFO). Methods: We performed a retrospective cohort analysis among 794 DFI episodes, including 339 DFO cases. Results: The median duration of antibiotic therapy after surgical debridement (including partial amputation) was 30 days (DFO, 30 days). Oral AMC was prescribed for a median of 20 days (interquartile range, 12‐30 days). The median ratio of oral AMC among the entire antibiotic treatment was 0.9 (interquartile range, 0.7‐1.0). After a median follow‐up of 3.3 years, 178 DFIs (22%) overall recurred (DFO, 75; 22%). Overall, oral AMC led to 74% remission compared with 79% with other regimens (χ 2 ‐test; P = 0.15). In multivariate analyses and stratified subgroup analyses, oral AMC resulted in similar clinical outcomes to other antimicrobial regimens, when used orally from the start, after an initial parenteral therapy, or when prescribed for DFO. Conclusions: Oral AMC is a reasonable option when treating patients with DFIs and DFOs.